Souvenir Development Based onLocal Wisdom and Community Participation in Puspo Ardhi Tourism Village - Ani Wijayanti (PolimdoSains, 2019)
Puspo Ardhi tourism village is a tourism village that is being developed, strategically located in the tourism area of ​​Kulon Progo. The quite basic problem and has not been resolved, namely the availability of souvenirs for tourists. Souvenirs are needed for the tourism village of Puspo Ardhi as a tourist attraction, promotional media, and improving the economy of local community. The research method used was descriptive qualitative, through direct observation in the tourism village of Puspo Ardhi. Data was obtained from various key informants including village officials, village tourism managers, and local communities. The results of the study were the identification of potential natural resources that could be used as basic resources for making souvenirs. The abundant natural resources in the tourism village of Puspo Ardi are bamboo plants, herbal plants, cassava, and koro beans. This study outlines a strategy for developing souvenirs using local resources with a participatory approach. The development of souvenirs based on local wisdom has several objectives, namely increasing the economic value of plants, providing business opportunities for the local community, and increasing family income.